2015
DOI: 10.1002/iid3.94
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2metabolites as a biomarker ofin vivomast cell activation in systemic mastocytosis and rheumatoid arthritis

Abstract: Mast cells (MCs) participate in diseases such as systemic mastocytosis (SM) and allergic conditions. Less well understood is the role of MCs in non‐allergic inflammatory disorders like rheumatoid arthritis (RA). Studying definitive roles for MCs in human diseases has been hampered by the lack of a well‐accepted biomarker for monitoring in vivo MC activation. This study aimed to investigate the utility of urinary tetranor PGDM (T‐PGDM) as a biomarker of in vivo MC activation in patients with SM, and apply this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Urinary t-PGDM is a potentially useful biomarker of in vivo activity of mast cells. 54 Furthermore, intestinal mucosal mast cells are critically involved in the development of food-induced allergic disorders. 55 A difference in LC-PUFA content between BM and formula might affect intestinal mucosal mast cells during infancy.…”
Section: Urinary Pg Metabolitesmentioning
confidence: 99%
“…Urinary t-PGDM is a potentially useful biomarker of in vivo activity of mast cells. 54 Furthermore, intestinal mucosal mast cells are critically involved in the development of food-induced allergic disorders. 55 A difference in LC-PUFA content between BM and formula might affect intestinal mucosal mast cells during infancy.…”
Section: Urinary Pg Metabolitesmentioning
confidence: 99%
“…We thought high levels of prostaglandin D2 (PGD2) could be responsible for higher tubular exosome release, and a high level of PLD in HαT patients can be responsible for a greater production of exosomes from mast cells. It has been previously shown that PGD2 urine metabolites are increased in patients with mast cell disorders and these metabolites can be used as biomarkers . In addition, PGE2 activates mast cell responses by inducing the mTORC2 pathway .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that PGD2 urine metabolites are increased in patients with mast cell disorders and these metabolites can be used as biomarkers. 47,48 In addition, PGE2 activates mast cell responses by inducing the mTORC2 pathway. 49 Prostaglandin E2 and Prostaglandin I2 are known to increase renal blood flow and glomerular filtration rate via vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…While levels of total unmodified prostaglandin in urine have been correlated with only a few diseases (e.g., cardiovascular disease (Raatz et al , ) and anaphylaxis (Lieberman, )), levels of prostaglandin metabolites in urine have attracted more scrutiny. High levels of the PGD 2 metabolite tetranor PGDM in urine have been correlated with Duchenne muscular dystrophy, systemic mastocytosis, rheumatoid arthritis, colitis, and colon cancer (Nakagawa et al , ,b; Iwanaga et al , ; Cho et al , ). High levels of urinary PGE 2 metabolite levels appear to be associated with colorectal adenoma (Shrubsole et al , ; Davenport et al , ), pancreatic cancer (Zhao et al , ), and breast cancer in postmenopausal women (Cui et al , ).…”
Section: Lipid Mediators In Body Fluidsmentioning
confidence: 99%